A Gratitude Exercise for Couples. Issue 3 (2nd July 2020) - Parnell, Kenneth J.; Wood, Nathan D.; Scheel, Michael J.
Abstract: When individuals experience gratitude they receive many benefits, including increased meaning in life, optimism, happiness, and greater connection to others. Multiple theorists and researchers citing the benefits of gratitude have proposed gratitude interventions for couples. However, research on intentionally practicing gratitude in the complex dynamics of intimate relationships remains sparse. This study piloted a two week-long gratitude exercise to explore if intentionally practicing gratitude could improve the quality of intimate relationships with 70 heterosexual couples. APIM models indicated a positive effect between the frequency of gratitude exercises and increased positive emotion, intimacy, and relationship satisfaction for women, but not for men, after accounting for relational satisfaction prior to the exercises. Implications for couples and psychoeducational settings are discussed.